2018
DOI: 10.3390/s18092780
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Retrieval of Broadband Dielectric Spectra

Abstract: A broadband soil dielectric spectra retrieval approach (1 MHz–2 GHz) has been implemented for a layered half space. The inversion kernel consists of a two-port transmission line forward model in the frequency domain and a constitutive material equation based on a power law soil mixture rule (Complex Refractive Index Model—CRIM). The spatially-distributed retrieval of broadband dielectric spectra was achieved with a global optimization approach based on a Shuffled Complex Evolution (SCE) algorithm using the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 73 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Scheuermann (2012) demonstrated that the TDR trace, especially the section between the first and second main reflection, contains information enabling the determination of the permittivity profile from the measured TDR signal, either in time domain or frequency domain. The classical approach to achieve this is based on the calculation of the wave propagation along the transmission line due to an incident voltage step (Lundstedt and He, 1996;Norgren and He, 1996;Feng et al, 1999;Heimovaara et al, 2004;Greco, 2006;Bumberger et al, 2018). An alternative approach was proposed by Schlaeger (2005) which allows the fast computation of soil moisture profiles along elongated probes from TDR signals, using either one-or two-ended measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Scheuermann (2012) demonstrated that the TDR trace, especially the section between the first and second main reflection, contains information enabling the determination of the permittivity profile from the measured TDR signal, either in time domain or frequency domain. The classical approach to achieve this is based on the calculation of the wave propagation along the transmission line due to an incident voltage step (Lundstedt and He, 1996;Norgren and He, 1996;Feng et al, 1999;Heimovaara et al, 2004;Greco, 2006;Bumberger et al, 2018). An alternative approach was proposed by Schlaeger (2005) which allows the fast computation of soil moisture profiles along elongated probes from TDR signals, using either one-or two-ended measurements.…”
Section: Introductionmentioning
confidence: 99%